Standarisasi Penanganan Kesehatan Pencegahan Covid-19 dihubungkan dengan Undang-Undang Nomor 36 Tahun 2009 Tentang Kesehatan - Muchammad Fauzan Mukhlis (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
Covid-19 is a deadly infectious disease and can be easily experienced by people who have low immunity. Until now there is no specific drug to treat cases of corona virus infection or Covid19. So to prevent the transmission, the government has implemented a large-scale social restriction (PSBB) policy, lockdown, total isolation or quarantine. These policies are basically to prevent disease transmission from sufferers to others, meaning that COVID-19 sufferers must be given special treatment by isolation or not mixing with other people. The government's efforts are basically referring to Law No. 36 of 2009 concerning Health in Chapter X concerning infectious diseases. In this case, the central government, regional governments and the community are responsible for preventing, controlling, and eradicating infectious diseases and their consequences. This is done to protect the public from contracting disease, to reduce the number of people who are sick, disabled and/or dead, and to reduce the social and economic impact of infectious diseases. Efforts to prevent, control, and handle infectious diseases are carried out through promotive, preventive, curative, and rehabilitative activities for individuals or the community. Prevention of transmission of infectious diseases must be carried out by the community, including people with infectious diseases, through clean and healthy living behavior.